DETECT THE FUNGI THAT ASSOCIATED WITH ZINNIA SEEDS AND IT, S EFFECT TO PLANT GROWTH STAGE - & Juber, Saeed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
This study was carried out to detect the Dematiceous hyphomycetes fungi that associated with Zinnia seeds and to test their pathogenicity and  effect on seed germination and foliage. Results of isolation and identification showed the existence of 8 species of these fungi associated with Zinnia seeds. Alternaria alternata was presented in 81.8% of seed samples with highly rate of frequency 77% in sample No.1. The preliminary test of the pathogenicity by cabbage seeds which included three separated experiments, showed that the 34 tested isolates caused a significant reduction in the rate of cabbage seeds germination except B18 isolate (Phoma eupyrena). Isolates B39 and H7 (Alternaria alternata ) were highly Pathogenic which the percentage of germination in their treatments were 0% compared to 98% in the control. Also test the results of effect of pathogenic isolates on Zinnia seeds germination by using blotter method which included two experiments, Showed that all isolates caused a significant reduction in Zinnia seeds germination in comparing with control treatments except  H6 isolate. two isolates B39 and H7(A. alternate ) gave a highly significant reduction which the percentage of germination in their treatments was 18% and 20%  respectively compared with control treatment. Under green house conditions, isolated H7 and B39 (A. alternate) , A13 (D. state of cochliobolus spicifer) and B8 (P. exigua ) were pathogenic for Zinnia plants with 100% disease incidence and 65-80% disease severity in comparing with control which the disease incidence and severity in their treatment was 2.5%. All these isolates significantly decreased the plant growth parameters.